The Association Between Foxp3 Polymorphisms and Risk of Graves' Disease: A Systematic Review and Meta-Analysis of Observational Studies - Li, Han-ning; Li, Xing-rui; Du, Ya-ying; Yang, Zhi-fang; Lv, Zheng-tao (Frontiers in Endocrinology, 2020)
Purpose: This systematic review and meta-analysis was carried out with the aim of investigating the relationship between Foxp3 polymorphisms (rs3761547, r3761548 and rs3761549) and the risk of Graves’ disease (GD). Methods: Four online database including PubMed, EMBASE, ISI Web of Science and CNKI were searched to identify observational studies that evaluated the association between Foxp3 polymorphisms and risk of GD. The strength of associations was indicated as odds ratio (OR) and corresponding 95% confidence interval (95%CI) under the allelic model. The Newcastle-Ottawa Scale was used to assess the methodological quality. Pre-specified subgroup analysis and sensitivity analysis were performed using RevMan 5.3 software. Publication bias was detected by Egger’s and Begg’s tests. Results: Eight case control studies involving 3104 GD patients and 3599 healthy controls were included. The methodological quality of included studies was considered to be moderate to high. The results of our meta-analysis supported no association of rs3761547 and risk of GD in Asians (OR: 1.07, 95%CI 0.97, 1.19, P=0.18). Evidence for rs3761547 and GD risk among Caucasians was still limited because only one study reported marginally increased risk of GD with the minor allele of rs3761547 (P=0.04). The variant allele of both rs3761548 (OR: 1.31, 95%CI 1.04, 1.64; P=0.02) and rs3761549 (OR: 1.30, 95%CI 1.03, 1.64; P=0.03) was associated with increased risk of GD among Asians, but neither polymorphism turned out to be related with GD among Caucasians. Conclusion: Rs3761548 and rs3761549 polymorphisms in Foxp3 were associated with risk of GD among Asians, possibly due to suppressed function of regulatory T cells and augmented autoimmune response. Their genetic effect among Caucasians remained to be confirmed by future large-scale and well-designed studies.